Harnessing Renewable Energy in Basra, Iraq: Study the Wind Energy - Al-Assadi, Zainab I. (Technium: Romanian Journal of Applied Sciences and Technology, 2024)
This research focuses on an important sector in the field of renewable energies, which is wind energy in Basra Governorate, where an area characterized by high grasses on flat land was chosen, and monthly wind speed data was used for thirty years during the period (1/1/1982 until (1/1/) 2021) and at an altitude of 10 m from the European Center for Weather Forecasting (ECMWF). To calculate the wind speed at several altitudes, the power law was used at several altitudes (70, 80, 90, 100) m, where it was possible to identify the wind behavior during the chosen time period, and a change was observed. Wind speed from one month to another, from one season to another, and from one year to another when changing the height of the wind turbine. The actual power extracted from the wind was also calculated and its effect by changing the height of the wind turbine. It was found that by increasing the height to 70, 80, 90, 100 meters, the power of the wind increases. Each time, its maximum value reached (6.36) megawatts at a height of 100 meters above the ground. By calculating wind energy at different heights, this study can be considered as attempt to develop and harnessing renewable energy in Basra, Iraq. ​